Implementation of the Presumption of Innocence Principle in Civil Procedure Law - Risa Amara; Putri Anggraeni Muslimah; Nafisa Sukma Dewi; Tegar Harbriyana Putra (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Every individual who is charged, suspected, detained, arrested, or brought before the court must be presumed innocent until a court decision establishes their guilt with permanent legal force. This principle is a fundamental pillar of the modern judicial system to ensure the protection of human rights and procedural fairness for all parties involved in the legal process. This study aims to comprehensively describe the application and regulation of the presumption of innocence principle within the context of civil procedural law, which has thus far received less attention and in-depth discussion compared to criminal law. By adopting a normative juridical approach, this research systematically examines and analyzes legal principles, statutory provisions, and relevant doctrines to clarify the philosophical foundations, historical development, and legal basis that form the primary foundation for protecting the rights of the parties involved in civil procedural law. The focus of this study is especially related to the provisions contained in the Civil Procedure Code and the Civil Code. This approach allows for a deeper and more holistic analysis of the implementation of the presumption of innocence and emphasizes its crucial role in maintaining the balance of interests and justice for all parties throughout the judicial process.